Tenuous Transcriptional Threshold of Human Sex Determination. I. SRY and Swyer Syndrome at the Edge of Ambiguity - Chen, Yen-Shan; Racca, Joseph D.; Weiss, Michael A. (Frontiers in Endocrinology, 2022)
Male sex determination in mammals is initiated by SRY, a Y-encoded transcription factor. The protein contains a high-mobility-group (HMG) box mediating sequence-specific DNA bending. Mutations causing XY gonadal dysgenesis (Swyer syndrome) cluster in the box and ordinarily arise de novo. Rare inherited variants lead to male development in one genetic background (the father) but not another (his sterile XY daughter). De novo and inherited mutations occur at an invariant Tyr adjoining the motif’s basic tail (box position 72; Y127 in SRY). In SRY-responsive cell lines CH34 and LNCaP, de novo mutations Y127H and Y127C reduced SRY activity (as assessed by transcriptional activation of principal target gene Sox9) by 5- and 8-fold, respectively. Whereas Y127H impaired testis-specific enhancer assembly, Y127C caused accelerated proteasomal proteolysis; activity was in part rescued by proteasome inhibition. Inherited variant Y127F was better tolerated: its expression was unperturbed, and activity was reduced by only twofold, a threshold similar to other inherited variants. Biochemical studies of wild-type (WT) and variant HMG boxes demonstrated similar specific DNA affinities (within a twofold range), with only subtle differences in sharp DNA bending as probed by permutation gel electrophoresis and fluorescence resonance-energy transfer (FRET); thermodynamic stabilities of the free boxes were essentially identical. Such modest perturbations are within the range of species variation. Whereas our cell-based findings rationalize the de novo genotype-phenotype relationships, a molecular understanding inherited mutation Y127F remains elusive. Our companion study uncovers cryptic biophysical perturbations suggesting that the para-OH group of Y127 anchors a novel water-mediated DNA clamp.